THE EFFECT OF AL-BAYAN METHOD AND COGNITIVE DEVELOPMENT ON READING THE BEGINNING OF THE LETTERS HIJAIYAH CHILDREN OF GROUP B IN STATE KINDERGARTEN (TK) PEMBINA RANTAU, ACEH TAMIANG DISTRICT - Zakiah Assidiki; Sri Milfayetty; Evi Eviyani (SENSEI RESEARCH CENTER, 2021)
The aims of this research are (1) to determine the effect of the ability to read the beginning of hijaiyah letters taught by the Al-Bayan method compared to children who are taught by the Iqra' method at the Pembina Rantau State Kindergarten, Aceh Tamiang Regency. Children who have high cognitive development are higher than children with low cognitive development. (3) Knowing the interaction between the Al-Bayan Method and cognitive development on the ability to read the initial hijaiyah letters of group B children in TK Negeri Pembina Rantau, Aceh Tamiang Regency. Data analysis used the Tuckey-test. The results of the study show that (1) There is an influence on the ability to read the beginning of the hijaiyah letters taught by the Al-Bayan method compared to children who are taught by the Iqra' method at the Pembina Rantau State Kindergarten, Aceh Tamiang Regency. Where the results of reading the initial hijaiyah letters of students who are taught using the Al-Bayan learning method with an average value of 67.00 are higher than students who are taught using the Iqra' learning method with an average value of 54.50. (2) There is an effect of reading results of children who have higher cognitive development than children with low cognitive development. Where the average value of the results of reading the initial hijaiyah letters of students with high cognitive development is 65.50, while the average value of the results of early reading of the hijaiyah letter of students with low cognitive development is 58.00. (3) There is a significant interaction between learning methods and students cognitive development on the results of reading the beginning of hijaiyah letters that have cognitive development in group B in state kindergarten Pembina Rantau. Where there is an interaction with Fcount (20.01) > Ftable (4.96).